ASSESSING THE LIKELIHOOD OF VOLCANIC ERUPTION THROUGH ANALYSIS OF VOLCANOTECTONIC EARTHQUAKE FAULT-PLANE SOLUTIONS - Roman D.C.; Neuberg J.; Luckett R.R. (My University, 2006)
Episodes of volcanic unrest do not always lead to an eruption. Many of the commonly monitored signals of volcanic unrest, including surface deformation and increased degassing, can reflect perturbations to a deeper magma storage system, and may persist for years without accompanying eruptive activity. Signals of volcanic unrest can also persist following the end of an eruption. Furthermore, the most reliable eruption precursor, the occurrence of low-frequency seismicity, appears to reflect very shallow processes and typically precedes eruptions by only hours to days. Thus, the identification of measurable and unambiguous indicators that are sensitive to changes in the mid-level conduit system during an intermediate stage of magma ascent is of critical importance to the field of volcano monitoring. Here, using data from the ongoing eruption of the Soufrière Hills Volcano, Montserrat, we show that ~90° changes in the orientation of double-couple fault-plane solutions for high-frequency 'volcanotectonic' (VT) earthquakes reflect pressurization of the mid-level conduit system prior to eruption and may precede the onset of eruptive episodes by weeks to months. Our results demonstrate that, once the characteristic stress field response to magma ascent at a given volcano is established, a relatively simple analysis of VT fault-plane solutions may be used to make intermediate-term assessments of the likelihood of future eruptive activity. © 2006 Elsevier B.V. All rights reserved.
Keywords: FAULT-PLANE SOLUTIONS; SOUFRIèRE HILLS VOLCANO; VOLCANIC HAZARDS; VOLCANO MONITORING; VOLCANO-TECTONIC EARTHQUAKES